Identification and Analysis of Students' Misconceptions Using Three-Tier Multiple Choice Diagnostic Instruments on Thermochemistry Topic - Irfandi, Irfandi; Murwindra, Rosa; Musdansi, Dwi Putri; N, Wimbi Apriwanda; Hanri, Chuzairy (Universitas Muhammadiyah Mataram, 2022)
Misconceptions can prevent students from mastering the material more deeply. This is because misconceptions can hinder the process of receiving and integrating knowledge. Therefore, the teacher must identify the misconceptions that occur in students. This study was conducted to identify misconceptions about thermochemistry using a three-tier diagnostic test for students at senior high school with a total of 33 students. The research design used is descriptive research. The research subjects were determined by purposive sampling technique. Data collection used was three-tier multiple choice diagnostic test and interview. Data was analyzed using descriptive statistics with percentages and criteria for misconceptions. The results showed that 16.72% of students understood the content, 36.36% had misconceptions, guessed 18.54% and 28.27% did not understand the concept. Through this finding, in the hope is that teachers could analyze the causes of students' misconceptions, and find appropriate learning methods and media to reduce misconceptions occurred.